IMPROVING THE DIVERSIFICATION AND MODERNIZATION OF THE TOURISM INDUSTRY BASED ON THE CONCEPT OF MARKETING (Journal of Pharmaceutical Negative Results, 2022)
The article discusses the organizational and economic mechanisms for the development and diversification of tourism services, taking into account the formation of tourist areas based on the quality of services, target areas and marketing segmentation of topics.